2014
DOI: 10.12659/msm.892139
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Mean Platelet Volume and Neutrophil-to-Lymphocyte Ratio for Evaluation of Children with Familial Mediterranean Fever

Abstract: BackgroundFamilial Mediterranean fever (FMF) is an autoinflammatory disease characterized by recurrent attacks of serositis, fever, and rash. Clinical and subclinical inflammatory processes may contribute to atherosclerosis in FMF patients, with mean platelet volume (MPV) as a potential indicator for atherosclerosis risk and neutrophil-to-lymphocyte ratio (NLR) as a marker for subclinical inflammation in these patients. In this study, we investigated whether MPV can be used as an indicator for atherosclerosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Uluca et al conducted another study on 75 FMF patients in attack, 157 attack-free patients, and 77 healthy controls, in which they determined that mean MPV and platelet distribution width (PDW) value were not significantly different between the groups [26]. Similar to the present study, we found that there was no statistically significant difference in MPV levels between AA-FMF patients and the control group.…”
Section: Discussionsupporting
confidence: 85%
“…Uluca et al conducted another study on 75 FMF patients in attack, 157 attack-free patients, and 77 healthy controls, in which they determined that mean MPV and platelet distribution width (PDW) value were not significantly different between the groups [26]. Similar to the present study, we found that there was no statistically significant difference in MPV levels between AA-FMF patients and the control group.…”
Section: Discussionsupporting
confidence: 85%
“…MPV values were found higher even in attack-free FMF cases. However, some other investigators did not determine any increase in platelet volumes [23,24]. Only one research reported lower MPV values in cases having FMF [25].…”
Section: Discussionmentioning
confidence: 99%
“… 10 11 In children, NLR was found to differentiate between viral and bacterial pneumonia, 12 to be a useful diagnostic marker of acute appendicitis 13 and to predict an attack of familial Mediterranean fever in children already diagnosed with this condition. 14 …”
Section: Introductionmentioning
confidence: 99%